Brake reaction time before and after surgery for patients with sequestrectomy versus conventional microdiscectomy. (February 2020) - Thaler, Martin; Putzer, David; Lindtner, Richard; Krappinger, Dietmar; Haid, Christian; Obwegeser, Alois; Lechner, Ricarda
Highlights: Breaking response time reduces after sequestrectomy and microdiscectomy surgery. No driving abstinence is required after sequestrectomy or microdiscectomy surgery. After 30 days breaking response time of patients are comparable to healthy people. Abstract: The aim of this study was to compare the effects of sequestrectomy versus conventional microdiscectomy on breaking response time (BRT) for lumbar disc herniation (LDH). BRT is the key factor for return to drive recommendations after surgery. A prospective clinical study was conducted. Patients aged 25–65 years who underwent surgery for lumbar disc herniation and held a valid motorcar driving license were recruited in a single institution. The patients were assessed before surgery, immediately after the surgery and at the follow up examination 30 days post-surgery. BRT was measured using a driving simulator, a visual analogue scale (VAS) was used for pain assessment. BRT values were compared with BRT values of a healthy control group. In patients treated with microdiscectomy BRT reduced from 749 (±223) msec before surgery to 649 (±223) msec immediately after the surgery. In the sequestrectomy group BRT reduced from 852 (±561) msec before surgery to 693 (±173) msec immediately after the surgery. BRT at follow up was 610 (±145) msec for patients treated with microdiscectomy and 630 (±98) msec for patients operated with sequestrectomy. BRT for healthy controls was 487 (±116) msec. Pain improved significantly for both patient samples. Sequestrectomy and microdiscectomy were associated with similar effects on pain and BRT after surgery. There was no statistically significant difference between BRT of both patient samples at 30 days follow up examination. Both surgical techniques showed a positive effect on BRT. No statistically significant difference between sequestrectomy and microdiscectomy on BRT could be found.